Impact of Player Unknown’s Battlegrounds (PUBG) Method Toward Vocabulary Mastery for Senior High School Students - Hesthi, Tanaffasa; Budiharso, Teguh (Jurnal Sosial Teknologi, 2025)
This research aimed to investigate the impact of the Player Unknown’s Battlegrounds (PUBG) game on students’ vocabulary acquisition. The study utilized an ex post facto experimental design with a post-test-only approach, involving a sample of 34 twelfth-grade students from SMK Rosma Karawang. The participants were divided into two groups: those who regularly played PUBG and those who did not. Data were gathered through a vocabulary proficiency test and analyzed using SPSS 26 with an independent sample t-test. The results indicate that students who played PUBG demonstrated significantly higher vocabulary mastery than those who did not play. These findings suggest that PUBG can be an engaging and interactive supplementary tool for vocabulary development.